Can Low-Carbon Technological Innovation Reduce Haze Pollution?—Based on Spatial Econometric Analysis - Jin, Shunlin; Wang, Weidong; Qalati, Sikandar Ali; Zhang, Caijing; Lu, Na; Zhu, Guyu; Wu, Jiahui (Frontiers in Environmental Science, 2022)
Exploring the co-benefits of low-carbon tech-innovation in response to climate change on haze pollution is an important foundation for China’s ecological construction, and also a key path to achieve the common goal of carbon and haze reduction. Based on STIRPAT model and EKC hypothesis, the dynamic Spatial Dubin Model (SDM) is constructed to empirically analyze the co-benefits and mechanism of low-carbon tech-innovation on haze pollution in 30 Chinese provinces from 2006 to 2018. The results show that : (1) haze pollution in different regions of China shows significant temporal and spatial correlation. (2) China’s low-carbon tech-innovation brings co-benefits of haze pollution suppression and long-term positive externalities between regions. (3) Environmental policy and industrial structure play a moderating and mediating role respectively, the former produces the “innovation offset” effect. (4) Both types of low-carbon tech-innovation can suppress haze pollution, but gray tech-innovation shows better haze control ability and cross-regional diffusion ability. Therefore, a long-term mechanism for haze control and joint prevention and control should be established to prevent the rebound and agglomeration of haze. Balance the development of different types of low-carbon technologies to achieve coordinated control of carbon emissions and haze.